Marked point process variational autoencoder with applications to unsorted spiking activities. - Ryohei Shibue; Tomoharu Iwata (PLoS Computational Biology)
Spike train modeling across large neural populations is a powerful tool for understanding how neurons code information in a coordinated manner. Recent studies have employed marked point processes in neural population modeling. The marked point process is a stochastic process that generates a sequence of events with marks. Spike train models based on such processes use the waveform features of spikes as marks and express the generative structure of the unsorted spikes without applying spike sorting. In such modeling, the goal is to estimate the joint mark intensity that describes how observed covariates or hidden states (e.g., animal behaviors, animal internal states, and experimental conditions) influence unsorted spikes. A major issue with this approach is that existing joint mark intensity models are not designed to capture high-dimensional and highly nonlinear observations. To address this limitation, we propose a new joint mark intensity model based on a variational autoencoder, capable of representing the dependency structure of unsorted spikes on observed covariates or hidden states in a data-driven manner. Our model defines the joint mark intensity as a latent variable model, where a neural network decoder transforms a shared latent variable into states and marks. With our model, we derive a new log-likelihood lower bound by exploiting the variational evidence lower bound and upper bound (e.g., the χ upper bound) and use this new lower bound for parameter estimation. To demonstrate the strength of this approach, we integrate our model into a state space model with a nonlinear embedding to capture the hidden state dynamics underlying the observed covariates and unsorted spikes. This enables us to reconstruct covariates from unsorted spikes, known as neural decoding. Our model achieves superior performance in prediction and decoding tasks for synthetic data and the spiking activities of place cells.